Media kipas beredukasi sebagai inovasi promosi kesehatan untuk meningkatkan pengetahuan pasien diabetes mellitus - Wella Juartika; Jhon Feri; Lyara Herniva Yudistira; Syindi Fradila; Tandika Ap Rais (Nur Science Institute, 2025)
This study aimed to determine the effect of using an educational fan as a health promotion medium on improving patients' knowledge about Diabetes Mellitus. The background of this research was based on the low level of patients' understanding regarding self-management of Diabetes Mellitus, which contributes to poor treatment adherence and increased risk of complications. This study employed a pre-experimental design with a one-group pretest-posttest approach. A total of 30 patients with Diabetes Mellitus were selected using purposive sampling. The intervention was conducted by providing health education through an educational fan containing visual messages and brief texts about diet management, physical activity, and medication adherence. These findings indicate that the educational fan is an effective, simple, and attractive health promotion tool for enhancing patients' knowledge of Diabetes Mellitus management.